(untitled) (Journal of Hama University, 2024)
The study was traveled to determine the prevalence of chronic mastitis in dairy herds in Syria, and determination of the most responsible bacteria of inducing this type of inflammation and study of some potential risk factors associated with chronic mastitis in dairy herds. It was collected 1000 milk samples from effected chronic mastitis during the period from November 2020 to June 2022. Results reported that the absolute frequency to effect cow with chronic mastitis in Syria regions with 855 dairy cows with prevalence %11.07.The morbidity is distributing in vary quarters in cattle the major proportion was in back quarters –right and left many of causal agents bacteria were isolated it was the higher prevalence percentages with Staphylococcus aureus as percentage prevalence %29.43 follow by Escherichia coli as percentages prevalence as %28.75 follow by Staphylococcus epidermidis as percent %14.03 and Streptococcus agalactiae as percent %8.63 and Staphylococcus Saprophticus as percent %5.10 and Streptococcus dysagalactiae as percent %4.41 , Klebsiela as percent %4.12 Staphylococcus chromognes as percent %3.92 and Pseudomanas as percent %1.07. It was studied some potential risk factors associated with occurrence of chronic mastitis with dairy cattle herds in Syria. The occurrence of mastitis cows associated with group of risk factors ,as effected mast and teats, and Adrienne ages in cows, relating mast forms, cylindrical teats forms, in addition to dis cleaning in cattle house. The lactation dairy first stage was higher in occurrence of chronic mastitis.